2014
DOI: 10.5194/acp-14-12143-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of stabilized Criegee intermediates (sCIs) from isoprene and monoterpene ozonolysis toward SO<sub>2</sub> and organic acids

Abstract: Abstract. Oxidation processes in Earth's atmosphere are tightly connected to many environmental and human health issues and are essential drivers for biogeochemistry. Until the recent discovery of the atmospheric relevance of the reaction of stabilized Criegee intermediates (sCIs) with SO 2 , atmospheric oxidation processes were thought to be dominated by a few main oxidants: ozone, hydroxyl radicals (OH), nitrate radicals and, e.g. over oceans, halogen atoms such as chlorine. Here, we report results from labo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 45 publications
11
104
0
2
Order By: Relevance
“…In addition, SCI react with a number of other atmospheric species, e.g., H 2 O, SO 2 , NO 2 , carboxylic acids, as well as carbonyl and hydroxyl compounds. 5,45,[66][67][68]72,[93][94][95] Bimolecular reactions with these scavengers, in particular H 2 O, have been suggested to be the dominant loss pathway of some SCIs in the atmosphere. 45,67,72 However, in the present study, water vapor was shown to increase new particle formation while decreasing the total mass.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SCI react with a number of other atmospheric species, e.g., H 2 O, SO 2 , NO 2 , carboxylic acids, as well as carbonyl and hydroxyl compounds. 5,45,[66][67][68]72,[93][94][95] Bimolecular reactions with these scavengers, in particular H 2 O, have been suggested to be the dominant loss pathway of some SCIs in the atmosphere. 45,67,72 However, in the present study, water vapor was shown to increase new particle formation while decreasing the total mass.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…Moreover, in some circumstances scavenging of SCI may not necessarily suppress particle formation. For example, in the presence of SO 2 , the reactions between SCI and SO 2 can lead to the formation of H 2 SO 4 , 5,74,93,96,97 an important nucleation precursor. 98,99 A quantitative evaluation of the atmospheric importance of RO 2 + SCI reactions is not possible at the moment because of the large uncertainties in the rate constants for bimolecular reactions of SCI, 45,67 especially those of RO 2 + SCI reactions for which experimental data are not available.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…Those measurements were conducted at 50% relative humidity (RH) and the derived sCI yield from the reaction between α-pinene and ozone was determined to be 0.15±0.07 and the ratio between the loss term 25 and ksCI+SO2 was (2.0±0.4) ×10 12 molecules cm -3 . Sipilä et al (2014) also found that in the case of α-pinene and limonene the ratio kloss / ksCI+SO2 was nearly independent of the relative humidity therefore we neglected the difference in RH of the experiments shown here (38%) compared to the experiments at TROPOS-LFT (50%). The temperature was 278 K in the CLOUD experiments whereas it was 293 K in the previous experiments.…”
Section: The Simulations Of Sci and Hom Concentrationsmentioning
confidence: 97%
“…Recent studies (Berndt et al, 2012;Mauldin III et al, 2012;Welz et al, 2012) with new experimental methods have shown up to four orders of magnitude higher reaction rate constants for the reaction between a sCI and SO2 compared to previous estimates. Also differences between the reactivity of sCI derived from different alkenes and their reactivity towards 5 SO2, water and several other atmospheric compounds has been emphasized (Berndt et al, 2014a;Sipilä et al, 2014;Taatjes et al, 2013;Vereecken et al, 2012Vereecken et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation